2017
DOI: 10.1016/j.jhep.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Tremelimumab in combination with ablation in patients with advanced hepatocellular carcinoma

Abstract: Background & Aims Tremelimumab is a fully human monoclonal antibody that binds to cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) on the surface of activated T lymphocytes. Ablative therapies induce a peripheral immune response which may enhance the effect of anti-CTLA4 treatment in patients with advanced hepatocellular carcinoma (HCC). This study aimed to demonstrate whether tremelimumab could be combined safely and feasibly with ablation. Methods Thirty-two patients with HCC were enrolled: male:female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
544
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 692 publications
(558 citation statements)
references
References 23 publications
12
544
0
2
Order By: Relevance
“…These locoregional therapies are particularly beneficial when the levels of cancer antigens are negligible because of poor antigen release. The results of combination therapy with an anti-CTLA-4 antibody and locoregional therapy in advanced HCC were recently published [14]. The NCT01853618 study evaluated the efficacy of adjuvant therapy with tremelimumab (anti-CTLA-4 antibody) after RFA or TACE in several, but not all, HCC nodules, with favorable outcomes, including a partial response rate of 26%, time to tumor progression of 7.4 months, and overall survival of 12.3 months.…”
Section: Combination Of Immune Checkpoint Inhibitors With An Existingmentioning
confidence: 99%
“…These locoregional therapies are particularly beneficial when the levels of cancer antigens are negligible because of poor antigen release. The results of combination therapy with an anti-CTLA-4 antibody and locoregional therapy in advanced HCC were recently published [14]. The NCT01853618 study evaluated the efficacy of adjuvant therapy with tremelimumab (anti-CTLA-4 antibody) after RFA or TACE in several, but not all, HCC nodules, with favorable outcomes, including a partial response rate of 26%, time to tumor progression of 7.4 months, and overall survival of 12.3 months.…”
Section: Combination Of Immune Checkpoint Inhibitors With An Existingmentioning
confidence: 99%
“…It was reported that a phase II study of tremelimumab as a single agent to treat HCC revealed a PR of 17.6%, a median TTP of 6.48 months, and a median overall survival of 8.2 months [25] . On the contrary, Duffy et al have reported the effect of tremelimumab, an anti-CTLA-4 antibody, in combination with RFA or TACE in advanced HCC patients; 26.3% of patients showed a PR, a median TTP of 7.4 months, and an overall survival of 12.3 months [27] . Interestingly, tremelimumab in combination with ablation induced the accumulation of intratumoral CD8 + T cells.…”
Section: Combination Of Immune Checkpoint Inhibitors With Other Treatmentioning
confidence: 99%
“…Interestingly, tremelimumab in combination with ablation induced the accumulation of intratumoral CD8 + T cells. Depending on the treated region, ablation induced a decrease in tumor volume as well, leading to the release of tumor-associated antigens from HCC cells and activated CD8 + T cells, which in turn could have enhanced the antitumor effect of tremelimumab to tumors at a distance [27] . The effectiveness of tremelimumab at lower doses, in combination with RFA or TACE, indicates that immune checkpoint inhibitors are more effective in combination with other conventional treatments, rather than as a single agent.…”
Section: Combination Of Immune Checkpoint Inhibitors With Other Treatmentioning
confidence: 99%
“…The safety profile and antitumor and antiviral effect, have been tested by the usage of antibody, Tremelimumab (CP-675,206) which blocks the binding of CTLA-4, on advanced HCC with HCV-related cirrhosis [53]. The combined treatment of tremelimumab and tumor ablation for advanced HCC patients brings supporting clinical activity and causes expansion of intratumoral CD8 + T cells [54]. Similarly, PD-1 interactions with PD-L1 and PD-L2 inhibits the proliferation of T cells and restrains the release of cytokines [48].…”
Section: Cytotoxic T Lymphocytesmentioning
confidence: 99%